Anticancer activity of streptochlorin, a novel antineoplastic agent, in cholangiocarcinoma - Kwak TW; Shin HJ; Jeong YI; Han ME; Oh SO; Kim HJ; Kim DH; Kang DH (Dove Medical Press, 2015)
Tae Won Kwak,1,* Hee Jae Shin,2,* Young-Il Jeong,1 Myoung-Eun Han,3 Sae-Ock Oh,3 Hyun-Jung Kim,4 Do Hyung Kim,5 Dae Hwan Kang1 1Biomedical Research Institute, Pusan National University Hospital, Busan, 2Marine Natural Products Chemistry Laboratory, Korea Institute of Ocean Science and Technology, Ansan, 3Department of Anatomy, School of Medicine, Pusan National University, Gyeongnam, 4Genewel Co Ltd. Gyeonggi-do, 5School of Medicine, Pusan National University, Yangsan, Gyeongnam, Republic of Korea *These authors contributed equally to this work Background: The aim of this study is to investigate the anticancer activity of streptochlorin, a novel antineoplastic agent, in cholangiocarcinoma. Methods: The anticancer activity of streptochlorin was evaluated in vitro in various cholangiocarcinoma cell lines for apoptosis, proliferation, invasiveness, and expression of various protein levels. A liver metastasis model was prepared by splenic injection of HuCC-T1 cholangiocarcinoma cells using a BALB/c nude mouse model to study the systemic antimetastatic efficacy of streptochlorin 5 mg/kg at 8 weeks. The antitumor efficacy of subcutaneously injected streptochlorin was also assessed using a solid tumor xenograft model of SNU478 cells for 22 days in the BALB/c nude mouse. Results: Streptochlorin inhibited growth and secretion of vascular endothelial growth factor by cholangiocarcinoma cells in a dose-dependent manner and induced apoptosis in vitro. In addition, streptochlorin effectively inhibited invasion and migration of cholangiocarcinoma cells. Secretion of vascular endothelial growth factor and activity of matrix metalloproteinase-9 in cholangiocarcinoma cells were also suppressed by treatment with streptochlorin. Streptochlorin effectively regulated metastasis of HuCC-T1 cells in a mouse model of liver metastasis. In a tumor xenograft study using SNU478 cells, streptochlorin significantly inhibited tumor growth without changes in body weight when compared with the control. Conclusion: These results reveal that streptochlorin is a promising chemotherapeutic agent to the treatment of cholangiocarcinoma. Keywords: streptochlorin, cholangiocarcinoma, chemotherapeutic agent, invasion, metastasis